Anomalous origin of the left coronary artery from the right pulmonary artery with intramural aortic trajectory. Clinicosurgical diagnostic implications - Atik,Edmar (1999)
OBJECTIVE: Anomalous origin of the left coronary artery from the right pulmonary artery (AOLCARPA), is a rare entity that is usually associated with other defects. Of the 20 cases of AOLCARPA reported in the literature, 14 (70%) had associations. We describe four patients with AOLCARPA without associated defects, but with a peculiar intramural aortic trajectory. METHODS: Fifty-five patients with anomalous origin of the left coronary artery were operated upon at INCOR-FMUSP. Four of the patients had the anomalous origin from the right pulmonary artery (RPA) without associated defects but with intramural aortic trajectory. Clinical and laboratory examinations were analyzed, as well as surgical findings. RESULTS: All patients had congestive heart failure (CHF) and 3 also had angina pectoris. Two patients had a murmur of mitral regurgitation, signs of myocardial infarction on the ECG and cardiomegaly. The shortening fraction varied from 9% to 23%. The hemodynamic study confirmed the diagnosis of anomalous origin of the coronary artery, but the intramural trajectory and the origin from the RPA were established only at surgery. In 3 patients, the technique of side-to-side anastomosis was performed with a good outcome. One patient, who underwent end-to-side anastomosis, died 6 months after the surgery. CONCLUSION: Association with other defects usually occurs in the AOLCARPA, and the intramural aortic trajectory is difficult to clinically diagnose but easy to surgically correct.